PENGARUH FASILITAS SEKOLAH TERHADAP PEMAHAMAN DAN PENERAPAN KURIKULUM MERDEKA OLEH GURU - Farid Tri Febrian; Intan Putri Kamilah; Ruth Maret Tasya Raja Gukguk; Muhammad Jaya Adi Putra; Mutia Yulita Sari (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This study aims to analyze the impact of school facilities on the understanding and implementation of the Merdeka Curriculum at SDN 188 Pekanbaru. The Merdeka Curriculum emphasizes project-based and technology-driven learning, requiring adequate educational facilities. This research employs a qualitative method with data collected through direct observation and in-depth interviews with five teachers. The findings reveal that while there have been improvements in physical facilities, such as classrooms and libraries, the lack of digital facilities and technology-based teaching aids is a major barrier to the curriculum’s implementation. Teachers reported that limited access to devices such as computers, projectors, and the internet reduces the effectiveness of the learning process. These obstacles also hinder interactive engagement between teachers and students and prevent the application of project-based learning, which is a core component of the Merdeka Curriculum. The teachers also highlighted the need for training in the use of technology to improve the quality of teaching. In conclusion, adequate technological facilities and teacher training are crucial for the optimal implementation of the Merdeka Curriculum and to fully develop students' potential.